1990
DOI: 10.2134/jeq1990.00472425001900020020x
|View full text |Cite
|
Sign up to set email alerts
|

Sewage Sludge Effects on Soil and Plant Quality in a Degraded, Semiarid Grassland

Abstract: A major problem affecting grassland productivity in the semiarid southwestern USA is the low quantity of soil organic matter and plant-available N. In this study, dried, anaerobically digested sewage sludge was applied at three rates (22.5, 45, and 90 Mg ha~') to a degraded semiarid grassland site to determine the effects of sludge on soil chemical and heavy metal properties, and vegetative yields and quality over two growing seasons. Most nutrients, including soil N, P, and K, increased linearly as a result o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 0 publications
4
57
0
1
Order By: Relevance
“…1), and was associated with reduced cover in other life forms such as perennial forbs and annual grasses. Others have found similar results with biosolids land application to semi-arid grasslands (Fresquez et al, 1990a(Fresquez et al, , 1990b. The stimulation of perennial grass growth by composted biosolids resulted in a slight reduction in plant species diversity (i.e.…”
Section: Plant Community Characterizationmentioning
confidence: 52%
See 1 more Smart Citation
“…1), and was associated with reduced cover in other life forms such as perennial forbs and annual grasses. Others have found similar results with biosolids land application to semi-arid grasslands (Fresquez et al, 1990a(Fresquez et al, , 1990b. The stimulation of perennial grass growth by composted biosolids resulted in a slight reduction in plant species diversity (i.e.…”
Section: Plant Community Characterizationmentioning
confidence: 52%
“…Fresquez et al (1990a) also observed a decrease in soil pH and an increase in soil N with increasing biosolids rate applied to a semiarid grassland in New Mexico.…”
Section: Soil Chemical Characterizationmentioning
confidence: 73%
“…Several investigators reported that the application of organic matter to different soils significantly increased their organic matter contents and improved the soil physical and chemical properties (Fresquez et al, 1990;Rehan et al, 2004;Youssef, 2011;Hadad et al, 2015). Also, Rashid et al, 2004 reported that, all phosphate solubilizing microorganisms (PSM) strains utilize carbon sources for production of organic acids…”
Section: Organic Matter (Om %) Contentmentioning
confidence: 99%
“…But regardless to the RE of each product, plants responded positively to all biosolids applied to both soils and reached yield plateaus for all treatments on the Spodosol (Figure 1). Osborne, (1996), Süss, (1997 and Fresquez et al, (1990) found sewage sludge being more effective for plant growth than fertilizers. On mining spoils, sewage sludge also out-performed the standard rehabilitation technique based on chemical fertilization (Phillips, 1994).…”
Section: Ryegrass Yield On Spodosol Soilmentioning
confidence: 99%